Studi Kelayakan Penerapan Heterogen Network 5g Di Kecamatan Pekanbaru Kota - Syafitri, Elsa; Rahayu, Yusnita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This paper proposes feasibility the implementation of heterogeneous networks 5G in sub-district of Pekanbaru Kota. Het-Net is a network topology with technology of cell densification that spreads several levels of cellular communication networks. This topography also requires several of steps,i.e. sychas cells data collection, network plan by the capacity, network mapping based on the network coverage and network mapping by Software (e.g. open signal, google earth and MapInfo). Thees steps are to get voronoi diagramm and find out the point of id-cell and the areas which are not covered by the existing tower. 5G mapping is based on calculations, that resulted 5 new cells 5G tower with 0,419 Km of radius and 9 the cells from the existing tower. Based on the customers prediction, the design has fulfilled on the demand until 2020.Keywords: Heterogen Network, Mapping, Planning Capacity and Planning Coverage